Knowledge, Awareness and Practice of Blood Culture Collection Among Clinical Staff in A Tertiary Hospital in the UK - Nnamani, Nnaemeka; Wickremasinghe, Darshana (Journal of Nepalese Society of Critical Care Medicine, 2026)
Background and aims: Blood culture (BC) is an essential diagnostic tool for bloodstream infections. However, inappropriate collection technique continues to affect the quality of BC results due to contamination, potentially leading to improper use of antimicrobial therapy. Appropriate collection technique and adherence to standard protocols are key to minimize the rate of BC contamination. This study aims to evaluate the knowledge, awareness and practice regarding BC collection among clinical staff (CS) at a UK tertiary hospital. Methods: A cross-sectional questionnaire-based study was conducted among CS of a UK hospital. Data were collected using a questionnaire and analysed through descriptive statistics. Results: A total of 196 CS participated. Participants were mostly from the ward (55.61%) while the same day emergency had the fewest participants of less than 5%. Less than 50% had awareness of hospital BC policy, while more than 50% showed understanding. However, there was variable knowledge on principles guiding BC, such as the timeline required to transport a sample (12.76%), skin disinfection time (13.78%), and supervision requirements for competence (56.12%). Although the majority of CS (69.9%) showed knowledge on collecting BC before other blood samples to avoid contamination and accuracy, only a third (35.20%) had knowledge of blood culture in relation to antibiotics administration. Nearly 40% of staff had never been trained before undertaking this procedure, while only 15% had been trained for less than 6 months. Conclusion: There were gaps in KAP of CS regarding BC which may explain the observed contamination rate of the center. Educational support, supervision and regular audit would be helpful in improving quality of BC.